Current insights of community mental healthcare for people with severe mental illness: A scoping review - van Genk, Caroline; Roeg, Diana; van Vugt, Maaike; van Weeghel, Jaap; Van Regenmortel, Tine (Frontiers in Psychiatry, 2023)
Background For the last four decades, there has been a shift in mental healthcare toward more rehabilitation and following a more humanistic and comprehensive vision on recovery for persons with severe mental illness (SMI). Consequently, many community-based mental healthcare programs and services have been developed internationally. Currently, community mental healthcare is still under development, with a focus on further inclusion of persons with enduring mental health problems. In this review, we aim to provide a comprehensive overview of existing and upcoming community mental healthcare approaches to discover the current vision on the ingredients of community mental healthcare. Methods We conducted a scoping review by systematically searching four databases, supplemented with the results of Research Rabbit, a hand-search in reference lists and 10 volumes of two leading journals. We included studies on adults with SMI focusing on stimulating independent living, integrated care, recovery, and social inclusion published in English between January 2011 and December 2022 in peer-reviewed journals. Results The search resulted in 56 papers that met the inclusion criteria. Thematic analysis revealed ingredients in 12 areas: multidisciplinary teams; collaboration within and outside the organization; attention to several aspects of health; supporting full citizenship; attention to the recovery of daily life; collaboration with the social network; tailored support; well-trained staff; using digital technologies; housing and living environment; sustainable policies and funding; and reciprocity in relationships. Conclusion We found 12 areas of ingredients, including some innovative topics about reciprocity and sustainable policies and funding. There is much attention to individual ingredients for good community-based mental healthcare, but very little is known about their integration and implementation in contemporary, fragmented mental healthcare services. For future studies, we recommend more empirical research on community mental healthcare, as well as further investigation(s) from the social service perspective, and solid research on general terminology about SMI and outpatient support.